Making the connection: expanding the role of restoration genetics in restoring and evaluating connectivity. Issue 3 (12th March 2018) - Proft, Kirstin M.; Jones, Menna E.; Johnson, Christopher N.; Burridge, Christopher P.
Abstract : The success of restoration activities is affected by connectivity with the surrounding landscape. From a genetic perspective, landscape connectivity can influence gene flow, effective size, and genetic diversity of populations, which in turn have impacts on the fitness and adaptive potential of species in restored areas. Researchers and practitioners are increasingly using genetic data to incorporate elements of connectivity into restoration planning and evaluation. We show that genetic studies of connectivity can improve restoration planning in three main ways. First, by comparing genetic estimates of contemporary and historical gene flow and population size, practitioners can establish historical baselines that may provide targets for restoration of connectivity. Second, empirical estimates of dispersal, landscape resistance to movement, and adaptive genetic variance can be derived from genetic data and used to parameterize existing restoration planning tools. Finally, restoration actions can also be targeted to remove barriers to gene flow or mitigate pinch‐points in corridors. We also discuss appropriate methods for evaluating the restoration of gene flow over timescales required by practitioners. Collaboration between restoration geneticists, ecologists, and practitioners is needed to develop practical and innovative ways to further incorporate connectivity into restoration practice.